Energy performance analytical review of semi-transparent photovoltaics glazing in the United Kingdom. (15th August 2022) - Musameh, Haytham; Alrashidi, Hameed; Al-Neami, Faris; Issa, Walid
Abstract: This work reviews the recent achieved advancement in semi-transparent photovoltaics (STPV) glazing systems, which are considered as a possible solution to improve the thermal performance of buildings. A numerical model was developed utilising EnergyPlus to investigate the impact of integrating STPV glazing systems in the United Kingdom. The simulation investigated the overall energy consumption under different Window-to-Wall ratio (WWR) for south-oriented STPV glazing systems with different transparencies and materials. The results indicated that employing clear double-glazing in small glazing situation at WWR = 30% would reduce the overall energy consumption by (7.5–26) % depending on the implemented STPV glazing systems. Furthermore, applying STPV glazing system in large glazing (WWR ≥70%) would lead to a decrease in the overall energy performance by 40% compared with the conventional clear double-glazing systems. However, utilising STPV glazing systems in medium-sized glazing is dependent on the solar material that is used. The results indicated that employing a-Si STPV glazing system is inefficient when the glazing cover (30% < WWR <70%) comparing to the clear double-glazing system. This result is a consequence of to the thermal and optical characteristics of a-Si solar cells. These characteristics would eventually lead to a higher heating and lighting requirements. Graphical abstract: Image 1 Highlights: In-depth analysis of the previous literature (section 3 /Literature review). A summery table that includes further literature. A numerical model has been developed to establish a case study in the United Kingdom. Investigate the effects that the transparency of STPV glazing systems and the WWR have on the overall energy performance.